Recommandation de l’UNESCO sur une science ouverte - UNESCO (UNESCO, 2021)
Keywords: Données ouvertes; Libre accès; Science ouverte

Prefigurative politics and social change: a typology drawing on transition studies - Törnberg, Anton (Distinktion, 2021)
Recent years have seen a surge of interest in prefigurative politics, which refers to the political strategies that model a future society on a micro level and aim to instantiate radical social change in and through practice. While most previous studies have focused on defining the concept and categorizing various types of prefiguration, this paper contributes by investigating under what circumstances prefiguration leads to revolutionary social change. The paper takes an original approach to these issues by turning to transition studies and the socio-technical change literature. This field focuses on the technical equivalence of prefiguration: namely, the relationship between small-scale niche innovations and large-scale technological transitions. Through theoretical discussions and empirical illustrations, this paper presents a typology of five transition pathways through which prefigurative strategies may result in a range of social change outcomes from reformative to revolutionary transformation.
Keywords: Changement social; Histoire; Innovation technologique; Libre accès; Mouvement social; Politiques; Science politique; Technologie; Transition